SYNERGETIC EFFECTS OF PHYSICOCHEMICAL PARAMETERS OF WATER ON THE PARASITIC EFFECTS OF Trichodina sp. SAMPLED FROM THE EPIDERMIS OF Channa punctatus IN RELATION TO ORGANIC POLLUTION OF RIVER SARASWATI (INDIA) (Applied Biological Research, 2023)
The impact of water pollution on aquatic biota and ecosystem health are  determined by the type and degree of water pollution. The present study was  aimed to assess the impact of degraded physicochemical regime of river  Saraswati in India on the parasitic load of Trichodina sp. obtained from Channa  punctatus. The overall water quality status of the polluted river was assessed by  using ten physicochemical parameters of water. A total of 404 fish were  examined for ciliate ectoparasite Trichodina sp. and prevalence, mean intensity  and abundance of parasitic load for each month determined. The parasitic load  of Trichodina sp. was significantly (p < 0.001) high in winter and negatively  correlated with temperature, free CO2, and biochemical oxygen demand BOD,  but positively correlated with electrical conductivity (EC). Fish health was  adversely affected by degrading water qualities and parasitic infection. A  ‘vicious cycle’ develops because of interplay among deteriorating water quality, withering fish immunological defence, and amplifying parasitic infection.
Keywords: Parasitic load; pollution; riverine health; Saraswati river; Trichodina sp; water parameters